Isolement et identification des bactéries lactiques à partir des produits laitiers traditionnels - OULD BEY, Baya; DAHMANE BOUNOUA, Kawther Hayet (My University, 2020)
In Algeria, as in the various other countries of the world, there are indigenous dairy products whose method of production derives from the cultural heritage of the population. These products come from the transformation of milk in order to extend its shelf life. Among the traditional Algerian dairy preparations: L’ben, Rayeb, J’ben, D’han and Yogurt. Lactic acid bacteria are a natural part of our environment and our diet. Lactic acid bacteria have long been recognized for the property of producing antimicrobial substances. Indeed, lactic acid bacteria have the distinction of synthesizing inhibitory substances. The objective of our research is to identify lactic acid bacteria isolated from the dairy products of the strait, and by studying the different technological properties. The study of macroscopic, microscopic, biochemical and physiological characteristics (fermentation type, sugar fermentation, growth at different temperatures and different NaCl) made it possible to orient the identification towards lactic acid bacteria. The researchers isolated and purified the strains of fermented milk products and then studied some technological skills in these isolates in order to assess their capacities for possible industrial use. So, they are based particularly on the evaluation of the proteolytic activity highlighted on GN medium with skimmed milk, flavoring and acidifying power. The results of the assessment of technological skills showed that these activities of interest are expressed in a very heterogeneous way. All the strains have an acidifying, proteolytic and antimicrobial power. The latter are an essential factor in dairy processing.
Keywords: Fermented milk products; lactic acid bacteria; technological characteristics; antimicrobial substances; proteolysis; acidifying power.